(untitled) (Ágora Journal, 2024)
Between the end of the 19th century and the beginning of the 20th, revue theater, a type of play belonging to the genre of light theater, became common in Brazil. Despite being honored by the most diverse social classes, these productions suffered severe criticism from individuals, who saw this plays as works of low artistic quality and aimed at a popular and non-selective audience. The objective of this article is to understand what were the main criticisms published in Rio de Janeiro, in relation to revue theater, in the first decades of the twentieth century. For this purpose, some publications available in Revista de Theatro e Sport, between the years 1909 and 1919, will be used.